Association between animal protein adequacy and anemia among pregnant women in Palembang, Indonesia - Kurniati, Ardesy Melizah; Oktharina, Eka Handayani; Aziz, Aryani; Faustina, Corinna (Indonesian Nutrition Association, 2025)
Background: Palembang City has the highest prevalence of anemia in South Sumatra, Indonesia. Protein contributes to hemoglobin formation and insufficient protein intake increases the risk of anemia. However, Sumatera studies on protein intake based on protein sources in pregnant women are still limited. Objective: This study aimed to examine the association between animal protein consumption and anemia prevalence in pregnant women. Methods: A cross-sectional analytic study was conducted from July to October 2024 at six public health centers and seven private midwife clinics selected to represent Palembang’s geographic diversity. A total of 62 pregnant women in their second or third trimester were recruited using consecutive sampling. Dietary intake was assessed via interviewer-administered 2×24-hour recalls on non-consecutive days. Protein intake was analyzed using modified NutriSurvey 2004 and categorized based on the Indonesian RDA. Hemoglobin levels were measured using venous blood samples and classified according to trimester-specific anemia thresholds. Bivariate analysis with Fisher’s exact test was used to examine the association between animal protein intake and anemia prevalence. Results: The Fisher Exact Test showed a statistically significant association between animal protein consumption levels and anemia in pregnant women in Palembang City (p = 0.018). The mean total protein intake was 80.40 ± 20.53 g/day, with animal and vegetable proteins contributing 40.22 ± 18.63 g/day and 40.91 ± 24.5 g/day, respectively. Mean hemoglobin level was 11.18 ± 1.17 g/dL. Conclusion: Sufficient consumption of animal protein was found to be more protective against the occurrence of anemia.